Vladimir Nabokov's comic quest for reality - Walenda, Marianne Kate (1980)
Nabokov once said that "reality" is "one of the few words which mean nothing without quotes." He has often expressed his scepticism as to whether it is ever possible to know a thing: all one can do is to collect as many facts and data about a thing as possible, accumulate information about it and thus try to get nearer its reality. But even though one may know a lot about an object, one can never know everything about it: "It's hopeless", Nabokov says and concludes, "... we live surrounded by more or less ghostly objects."